Determining pesticide residues in wheat flour by ultrahigh-performance liquid chromatography/quadrupole time-of-flight mass spectrometry with QuEChERS extraction. Issue 9 (2nd September 2019) - Song, Nho-Eul; Kim, Dan-Bi; Lim, Tae-Gyu; Lee, Yun-Yeol; Yoo, Miyoung; Nam, Tae Gyu
ABSTRACT: Pesticides are used to increase crop yields and preserve quality by protecting crops against pests; however, their overuse can adversely affect human health and the environment. Herein, we report the development of a multi-pesticide screening method using optimized QuEChERS coupled with liquid chromatography/quadrupole time-of-flight (QTOF) mass spectrometry for the analysis of 13 pesticides in wheat flour. Mass accuracies with errors of less than 2.4 ppm were obtained for all analysed pesticides, and the method provided satisfactory recovery and linearity. Repeatabilities of 0.3–12.7% and reproducibilities of 2.5–15.2% were observed in full-scan TOF mode. The performance of the developed full-scan TOF method was compared to that obtained in high-resolution multiple reaction monitoring (MRM-HR) mode. The limits of quantification for the full-scan TOF and MRM-HR modes ranged from 2 to 10, and 3 to 9 μg kg −1, respectively. The two quantification methods exhibited high sensitivities (limit of detections: 1–3 μg kg −1 in full-scan TOF, and 1–3 μg kg −1 for MRM-HR mode). No pesticide residues were detected when the developed method was applied to 22 real wheat flour samples.